Lipopolysaccharide-induced depression is associated with estrogen receptor-α/SIRT1/NF-κB signaling pathway in old female mice. (September 2021) - Jiang, Xi; Chen, Ziwei; Yu, Xuefeng; Chen, Jin; Sun, Chonglu; Jing, Changfeng; Xu, Lexing; Liu, Fuhe; Ni, Wenjuan; Chen, Lei
Abstract: The present study aims to investigate the influence of sex/age on depressive-like behaviors in lipopolysaccharide (LPS)-challenged mice model, and explore the underlying mechanisms. Tail suspension test and forced swimming test were used to evaluate the depressive-like behaviors. SIRT1 mRNA expression was assessed by PCR. Levels of 17β-estradiol (E2), SIRT1, NF-κB, tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β) and interleukin 6 (IL-6) were detected by enzyme linked immunosorbent assay (ELISA). In the behavior tests, under the same LPS stimulation, significant depressive-like behavior was observed in young male mice but not in young female mice, however, female mice were more likely to be depressed than male mice in the old age. Moreover, we found age-related depression difference existed only in female mice. In the experiments of mechanism exploration in old female mice, E2 improved LPS-induced depressive-like behavior, and simultaneously elevated SIRT1 levels and downregulated expressions of NF-κB and inflammatory cytokines in the hippocampus and frontal cortex. Interestingly, ERα inhibition, not ERβ inhibition, abolished E2's function. Additionally, SIRT1 antagonist also reversed E2's effects on depressive-like behavior and the expressions of NF-κB and inflammatory cytokines. These results suggested that E2 could protect the old female mice from depression via E2/ERα/SIRT1/NF-κB signaling pathway. In other words, LPS-induced depression was associated with ER-α/SIRT1/NF-κB signaling pathway in old female mice. By comparing the results of mechanism exploration in old male mice and old female mice and the different expression levels of E2, SIRT1, NF-κB and inflammatory cytokines in young female mice and old female mice, we speculate that the age or gender-related depression difference may be associated with the different activation levels of the ERα/SIRT1/NF-κB signaling pathway. Highlights: LPS-induced depression varies in mice with different ages and genders. The difference may be related to ERα/SIRT1 pathway.